Peningkatan Kecerdasan Intrapersonal Melalui Kegiatan Bermain Peran - Ayu Lestari (Idaarotul Ulum, 2020)
This study aims to improve early childhood intrapersonal intelligence through role-playing activities in kindergarten MI Karang Binangun. The method used is the method of action research. This study was conducted from August 1 to October 12, 2013. The method of analysis studies concluded with analysis using the percentage. Research declared successful if the percentage of intrapersonal intelligence assessment >20 after commencing the method of playing a role.in the first act, twenty students have increased intrapersonal intelligence. The highest percentage increase in the intrapersonal intelligence is achieved by PJ,AM,and FA subjects, at 95.59 %. Learning methods implemented by the teacher 's role to step to propose and discuss the situation, preparing roles, played a role, express the experience, and finish well. The purpose of this study has been achieved whit a maximum as expected.